A revised classification of the Icteridae (Aves) based on DNA sequence data - Remsen, J. V. Jr.; Powell, Alexis F. L. A.; Schodde, Richard; Barker, F. Keith; Lanyon, Scott M. (Zootaxa, 2016)
The higher-level classification of the New World blackbirds (Icteridae; Aves) has remained relatively stable for nearly a half-century, with most currently used classifications (e.g. Sibley & Monroe 1990; Jaramillo & Burke 1999; Fraga 2011; Remsen et al. 2015) following Blake’s (1968) delimitation and sequence of genera in the Peters Check-list of Birds of the World series. Early molecular studies (e.g., Lanyon 1992, 1994; Johnson & Lanyon 1999; Price & Lanyon 2002; Cadena et al. 2004) produced only minor modifications.